Ionic conductive hydrogel material, preparation method thereof and application of ionic conductive hydrogel material in electrochemical electrode

By developing an ionic conductive hydrogel material with high conductivity and mechanical properties, which is applied as a solid electrolyte to electrochemical electrodes, the problem that existing electrochemical testing technologies cannot quickly test old coatings, and rapid and reliable electrochemical testing of coatings is achieved.

CN119899484APending Publication Date: 2025-04-29CNOOC CHANGZHOU PAINT & COATINGS IND RES INST +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510169500.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing electrochemical testing techniques require liquid electrolytes and cannot be used for rapid electrochemical testing of old coatings on site.

Method used

An ionic conductive hydrogel material was developed to prepare a hydrogel material with high conductivity and mechanical properties through a combination of non-ionic water-soluble polymers, water-soluble ionic polymers, crosslinking agents, initiators and water retention agents, and applied it to electrochemical electrodes as a solid electrolyte.

Benefits of technology

Rapid electrochemical testing of new coats or in-service coatings is achieved, overcoming the limitations of liquid electrolytes required by traditional testing, with high sensitivity and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005273649980000041
    Figure BDA0005273649980000041
  • Figure BDA0005273649980000051
    Figure BDA0005273649980000051
  • Figure BDA0005273649980000052
    Figure BDA0005273649980000052
Patent Text Reader

Abstract

The invention discloses an ionic conductive hydrogel material as well as a preparation method and application thereof in an electrochemical electrode. The ionic conductive hydrogel material is prepared from the following raw materials in parts by weight: a nonionic water-soluble polymer, a water-soluble ionic polymer, a cross-linking agent, an initiator and a water-retaining agent. After the ionic conductive hydrogel is processed into a certain shape and soaked in a conductive ionic solution, the ionic conductive hydrogel can be used as a solid electrolyte to construct an electrochemical electrode suitable for on-site coating detection. The ionic conductive hydrogel disclosed by the invention has the advantages of optimal ionic conductivity, necessary mechanical property and mechanical stability, controllable swelling ratio and excellent chemical and electrochemical stability. The ionic conductive hydrogel is applied to an electrochemical electrode as a solid electrolyte, and high-concentration electrolytic active substances, namely conductive ions, are allowed to freely move in the hydrogel, so that the ionic conductivity of the hydrogel electrolyte is improved, and the reliability of the electrochemical electrode is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ion conductive hydrogels, and in particular to an ion conductive hydrogel material, a preparation method and an application in an electrochemical electrode. Background Art

[0002] Anti-corrosion coating plays a vital role in many fields. It can form a solid barrier on the surface of materials, effectively isolate corrosive media, thereby preventing corrosion and significantly extending the service life of materials. At the same time, anti-corrosion coatings customized for specific environments can also enhance the environmental adaptability of materials, enabling them to work stably in different climates, humidity and chemical environments, greatly reducing the burden and cost of maintenance work.

[0003] The quality of anti-corrosion coatings often determines the safety of equipment, so on-site inspection of anti-corrosion coatings is crucial. There are many methods for on-site inspection of coatings, including physical inspection methods, such as magnetic thickness measurement, ultrasonic thickness measurement, and evaluation of coating adhesion through the cross-cutting method and the pull-off method; chemical analysis methods, such as infrared spectroscopy analysis to identify coating composition, and pickling method to detect coating integrity; electrochemical tests, such as electrochemical impedance spectroscopy and polarization curve tests, to evaluate the anti-corrosion performance of coatings. In addition, it also includes a variety of technical methods such as appearance inspection, flexibility inspection, impact resistance inspection, porosity inspection, wear resistance inspection, and aging resistance inspection. Electrochemical detection is highly sensitive, rapid, and non-destructive, and is widely applicable to various metals, alloys, and conductive materials, providing a scientific basis for selecting appropriate materials and anti-corrosion measures. Electrochemical technology also has certain limitations in rapid on-site detection. Conventional electrochemical tests often require the presence of an electrolyte solution to provide a conductive path. Some electrochemical testing technologies currently available on the market require that the electrode be pre-buried in the coating, or that the coating to be tested be coated on the electrode surface, and the electrode be placed in the same service environment. The state of the coating on the electrode surface is regularly tested to represent the state of the coating to be tested. These detection methods are only applicable to newly applied coatings and cannot accurately evaluate the performance of old coatings.

[0004] Ion-conductive hydrogels have shown wide application potential in many fields due to their unique advantages. They not only have good ion conductivity and can achieve efficient charge transfer, but also have excellent biocompatibility and plasticity, and can adapt to various complex shapes and needs. In addition, ion-conductive hydrogels also show good water retention and mechanical strength, ensuring stability and durability in practical applications. Ion-conductive hydrogels are widely used in flexible electronic devices, biomedical sensors, wearable devices, and energy storage and conversion systems, providing strong support for technological innovation and performance improvement in these fields. Using ion-conductive hydrogels as electrolytes in electrochemical electrodes can realize conventional solution electrochemical testing in field environments, and evaluate the electrochemical anti-corrosion performance of coating materials, so as to evaluate the state of the coating and predict the coating life. Therefore, it is of great significance to develop an ion-conductive hydrogel material that can be used in electrochemical cells. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an ion conductive hydrogel material and a preparation method and an application in an electrochemical electrode. The ion conductive hydrogel of the present invention has optimal ion conductivity, necessary mechanical properties and mechanical stability, controllable swelling rate, and excellent chemical and electrochemical stability. The ion conductive hydrogel is used as a solid electrolyte in an electrochemical electrode, allowing a high concentration of electrolytically active substances, i.e., conductive ions, to move freely in the hydrogel, thereby improving the ion conductivity of the hydrogel electrolyte and ensuring the reliability of the electrochemical electrode.

[0006] In a first aspect, the present invention provides an ion conductive hydrogel material, which is realized by adopting the following technical scheme.

[0007] An ion conductive hydrogel material comprises the following raw materials in parts by weight: 10 to 20 parts of nonionic water-soluble polymer, 5 to 10 parts of water-soluble ionic polymer, 1 to 5 parts of crosslinking agent, 1 to 3 parts of initiator and 5 to 15 parts of water retaining agent.

[0008] Furthermore, the nonionic water-soluble polymer is selected from one or more of polyacrylic acid, polymethacrylic acid, polyacrylamide, polymethacrylamide, polyethylene glycol, polyoxyethylene, povidone, and polyethylene glycol diacrylate.

[0009] Furthermore, the water-soluble ionic polymer is selected from one or more of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, sodium dodecylbenzenesulfonate, sodium methylpropenesulfonate, ethyl cellulose, hydroxyethyl cellulose, methyl cellulose, quaternary ammonium hydroxyethyl cellulose ethoxylate, hydroxypropyl methyl cellulose, and carboxymethyl cellulose.

[0010] Furthermore, the crosslinking agent is selected from one or more of sodium carboxymethyl cellulose, ethylene glycol diacid, polyethylene glycol diacrylate, dimethyl acrylamide, dimethyl acrylamide, N,N'-methylene bisacrylamide, and polyoxypropylene ether triol.

[0011] Furthermore, the initiator is selected from one or more of potassium persulfate, sodium pyrosulfite, sodium metabisulfite, ammonium persulfate, N,N,N',N'-tetramethylethylenediamine, benzoin diethyl ether (Irgacure 651), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959), and 2,2'-azobis(2-methylpropionamidine) dihydrochloride.

[0012] Furthermore, the water retaining agent is one or more of gelatin, glycerol, agar, polysorbate, and potassium polyacrylate.

[0013] In a second aspect, the present invention provides a method for preparing an ion conductive hydrogel material, which is achieved by adopting the following technical scheme.

[0014] A method for preparing the above-mentioned ion conductive hydrogel material comprises the following steps:

[0015] S1. The nonionic water-soluble polymer, the water-soluble ionic polymer, and the crosslinking agent are added to deionized water and stirred to obtain a nonionic water-soluble polymer solution, a water-soluble ionic polymer solution and a crosslinking agent solution;

[0016] S2. Weigh the three solutions obtained in step S1 respectively, stir and mix them evenly, add a certain amount of water-retaining agent, continue to stir and mix evenly, and purge with nitrogen for 1 to 2 minutes;

[0017] S3. Add a certain amount of initiator to the mixed solution obtained in step S2 and continue stirring for 5 to 10 minutes;

[0018] S4. The uniformly mixed reaction solution in step S3 is transferred to a mold, and then the conditions for the cross-linking reaction are selected according to the type of initiator, and an ion conductive hydrogel material is obtained after the reaction.

[0019] Furthermore, in step S5, the cross-linking reaction includes thermal polymerization, UV polymerization, and pH-induced polymerization.

[0020] Furthermore, thermal polymerization is used to form a hydrogel system: the mold containing the reaction liquid is placed in an oven, reacted at 50-75°C for 10-20 minutes, and then taken out and left at room temperature overnight.

[0021] Furthermore, UV polymerization is used to form a hydrogel system: a transparent mold containing the reaction solution is placed in the irradiation chamber of a UV cross-linking instrument, UV irradiated for 30 to 60 seconds, and then taken out and placed at room temperature overnight.

[0022] Furthermore, pH-induced polymerization is used to form a hydrogel system: a strong base (pH = 10-12) or a strong acid (pH = 2-4) solution is added to the reaction solution, the mold containing the reaction solution is placed in an oven, and after reacting at 30-40°C for 10-15 minutes, it is taken out and placed at room temperature overnight; the strong base or strong acid solution includes sodium hydroxide, potassium hydroxide, and hydrochloric acid.

[0023] In a third aspect, the present invention provides an application of an ion conductive hydrogel material, which is achieved by adopting the following technical solution.

[0024] An application of the above ion-conductive hydrogel material as an ion-conductive electrolyte in the preparation of an electrochemical electrode for coating detection.

[0025] Further, the method for preparing the coating detection electrochemical electrode comprises the following steps:

[0026] a. processing the ion-conductive hydrogel into a desired shape and immersing it in a conductive ion solution for at least 24 hours to allow the ions to reach equilibrium;

[0027] b. The immersed hydrogel material is loaded into an electrochemical electrode, and an auxiliary electrode and a reference electrode are used to make an electrochemical electrode for coating electrochemical testing.

[0028] Furthermore, the conductive ion solution is selected from one or more of sodium chloride, potassium chloride, rubidium chloride, cesium chloride, magnesium chloride, strontium chloride, calcium chloride, barium chloride, potassium carbonate, potassium bicarbonate, potassium phosphate, potassium hydrogen phosphate, dipotassium hydrogen phosphate, 4-hydroxyethylpiperazineethanesulfonate potassium, and 1,4-piperazinediethanesulfonate dipotassium.

[0029] Furthermore, the auxiliary electrode is an inert electrode, which includes a platinum electrode and a graphite electrode.

[0030] Furthermore, the reference electrode is selected from Ag / AgCl, saturated calomel, mercuric oxide, and mercurous sulfate.

[0031] When in use, the bottom of the electrode is attached to the surface of the coating to be tested, and the coating is subjected to electrochemical tests such as AC impedance using a portable electrochemical workstation. When the hydrogel in the electrode loses water, it can be soaked in a conductive ion solution for a period of time and then rehydrated and continued to be used.

[0032] This application has the following beneficial effects.

[0033] (1) Non-ionic water-soluble polymers and water-soluble ionic polymers are combined with cross-linking agents, initiators, and water-retaining agents to prepare ion-conductive hydrogel materials under the action of heating, UV irradiation, pH induction, etc., and then immersed in a strong electrolyte solution to increase the ionic strength in the hydrogel material, thereby greatly improving its conductivity. The obtained ion-conductive hydrogel has excellent mechanical properties, high conductivity and electrochemical stability.

[0034] (2) The ion-conductive hydrogel prepared in the present application is used as a solid electrolyte to prepare an electrochemical electrode. This electrochemical electrode overcomes the disadvantage that traditional electrochemical testing requires liquid electrolytes and is not suitable for on-site coating electrochemical testing. It can realize rapid electrochemical testing of newly coated or in-service coatings. DETAILED DESCRIPTION

[0035] The present patent application is further described below in conjunction with embodiments.

[0036] The materials used in the preparation process of the following examples were not further processed unless otherwise specified and were purchased from commercial sources.

[0037] Example 1

[0038] Prepare 50wt.% polyacrylic acid solution, 50wt.% 2-acrylamido-2-methylpropanesulfonic acid sodium solution and 1wt.% N,N'-methylenebisacrylamide solution respectively, weigh the three solutions according to the table below, stir and mix evenly, add 40g glycerol, stir evenly and purge with nitrogen for 1min, add 5g of initiator potassium persulfate (1wt.%) and sodium pyrosulfite (1wt.%), continue stirring for 5min, transfer the mixed solution to the mold, and react in a 50℃ oven for 10min. After the temperature drops to room temperature, take out the mold and place it at room temperature overnight to obtain a hydrogel solid. Cut the hydrogel and soak it in 1mol / L sodium chloride solution for 24h to make an electrode. And use Ag / AgCl electrode as reference electrode and graphite rod as auxiliary electrode to test the electrochemical impedance spectrum of MC-EP-4 anti-corrosion coating (sprayed on 235Q carbon steel surface, coating thickness 100μm).

[0039]

[0040] Example 2

[0041] Prepare 50wt.% polyethylene glycol diacrylate solution, 30wt.% quaternary ammonium hydroxyethyl cellulose ethoxylate solution and 1wt.% N,N'-methylenebisacrylamide solution respectively, weigh the three solutions according to the table below, stir and mix evenly, add 40g glycerol, stir evenly and purge with nitrogen for 1min, add 5g initiator benzoin diethyl ether, continue stirring for 5min, transfer the mixed solution to a transparent mold, put it in the irradiation room of the UV cross-linking instrument, UV irradiate for 45s, take out the mold, and place it at room temperature overnight to obtain a hydrogel solid. Cut the hydrogel and soak it in 1mol / L sodium chloride solution for 24h to make an electrode. And use Ag / AgCl electrode as reference electrode and graphite rod as auxiliary electrode to test the electrochemical impedance spectrum of MC-EP-4 anti-corrosion coating (sprayed on 235Q carbon steel surface, coating thickness 100μm).

[0042]

[0043] Example 3

[0044] Prepare 50wt.% polyacrylamide solution, 50wt.% hydroxypropyl methylcellulose solution and 1wt.% polyoxypropylene ether triol solution respectively, weigh the three solutions according to the table below, stir and mix evenly, add 40g glycerol, stir evenly and purge with nitrogen for 1min, add 5g of initiator potassium sulfate (1wt.%) and sodium metabisulfite (1wt.%), continue stirring for 5min, transfer the mixed solution to the mold, and react in a 50℃ oven for 10min. After the temperature drops to room temperature, take out the mold and place it at room temperature overnight to obtain a hydrogel solid. Cut the hydrogel and soak it in 2mol / L 4-hydroxyethylpiperazine ethanesulfonic acid potassium solution for 24h to make an electrode. And use Ag / AgCl electrode as reference electrode and graphite rod as auxiliary electrode to test the electrochemical impedance spectrum of MC-EP-4 anticorrosion coating (sprayed on 235Q carbon steel surface, coating thickness 100μm).

[0045]

[0046] Performance Testing

[0047] The basic properties test results of the ion conductive hydrogel solid electrolytes obtained in Examples 1-3 of the present invention are as follows:

[0048] project Reference Standards Example 1 Example 2 Example 3 Conductivity (S / cm) GB / T31838.7-2021 0.12 0.08 0.11 Time required for 50% water loss (h) / 64 72 48 Tensile strength(MPa) GB / T1040-1992 1.2 0.8 1.1 Impedance (Ω·cm) GB / T39482.1-2023 35 44 32

[0049] The results of the electrochemical electrode test of the anti-corrosion coating prepared in Examples 1-3 of the present invention and the results of the conventional solution method electrochemical impedance test are as follows:

[0050] project Reference Standards Example 1 Example 2 Example 3 solution method Coating impedance (Ω·cm) GB / T39482.1-2023 <![CDATA[4.5×10 8 ]]> <![CDATA[3.7×10 8 ]]> <![CDATA[3.4×10 9 ]]> <![CDATA[1.5×10 9 ]]>

[0051] It can be seen from the above results that the ion conductive hydrogel solid electrolytes prepared in Examples 1-3 of the present invention have very high electrical conductivity, strong mechanical properties, and a relatively small impedance value. The water loss time is more than 48 hours, which can ensure continuous use on site. The impedance value of the anti-corrosion coating tested by the electrochemical electrode prepared based on the solid electrolyte is also close to the test value of the traditional solution method, and has high reliability.

[0052] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, all equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An ion conductive hydrogel material, characterized in that: The invention comprises the following raw materials in parts by weight: 10 to 20 parts of non-ionic water-soluble polymer, 5 to 10 parts of water-soluble ionic polymer, 1 to 5 parts of cross-linking agent, 1 to 3 parts of initiator and 5 to 15 parts of water retaining agent.

2. An ion conductive hydrogel material according to claim 1, characterized in that: The non-ionic water-soluble polymer is selected from one or more of polyacrylic acid, polymethacrylic acid, polyacrylamide, polymethacrylamide, polyethylene glycol, polyoxyethylene, povidone, and polyethylene glycol diacrylate.

3. The ion conductive hydrogel material according to claim 1, characterized in that: The water-soluble ionic polymer is selected from one or more of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, sodium dodecylbenzenesulfonate, sodium methylpropenesulfonate, ethyl cellulose, hydroxyethyl cellulose, methyl cellulose, quaternary ammonium hydroxyethyl cellulose ethoxylate, hydroxypropyl methyl cellulose, and carboxymethyl cellulose.

4. The ion conductive hydrogel material according to claim 1, characterized in that: The crosslinking agent is selected from one or more of sodium carboxymethyl cellulose, ethylene glycol diacid, polyethylene glycol diacrylate, dimethyl acrylamide, dimethyl acrylamide, N,N'-methylene bisacrylamide, and polyoxypropylene ether triol.

5. The ion conductive hydrogel material according to claim 1, characterized in that: The initiator is selected from one or more of potassium persulfate, sodium pyrosulfite, sodium metabisulfite, ammonium persulfate, N,N,N',N'-tetramethylethylenediamine, benzoin diethyl ether, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, and 2,2'-azobis(2-methylpropionamidine) dihydrochloride.

6. The ion conductive hydrogel material according to claim 1, characterized in that: The water retaining agent is one or more of gelatin, glycerin, agar, polysorbate and potassium polyacrylate.

7. A method for preparing the ion conductive hydrogel material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. The nonionic water-soluble polymer, the water-soluble ionic polymer, and the crosslinking agent are added to deionized water and stirred to obtain a nonionic water-soluble polymer solution, a water-soluble ionic polymer solution and a crosslinking agent solution; S2. Weigh the three solutions obtained in step S1 respectively, stir and mix them evenly, add a certain amount of water-retaining agent, continue to stir and mix evenly, and purge with nitrogen for 1 to 2 minutes; S3. Add a certain amount of initiator to the mixed solution obtained in step S2 and continue stirring for 5 to 10 minutes; S4. The uniformly mixed reaction solution in step S3 is transferred to a mold, and then the conditions for the cross-linking reaction are selected according to the type of initiator, and an ion conductive hydrogel material is obtained after the reaction.

8. Use of the ion conductive hydrogel material according to any one of claims 1 to 6 as an ion conductive electrolyte in the preparation of an electrochemical electrode for coating detection.

9. The use according to claim 8, characterized in that: The method for preparing a coating detection electrochemical electrode comprises the following steps: a. processing the ion-conductive hydrogel into a desired shape and immersing it in a conductive ion solution for at least 24 hours to allow the ions to reach equilibrium; b. The immersed hydrogel material is loaded into an electrochemical electrode, and an auxiliary electrode and a reference electrode are used to make an electrochemical electrode for coating electrochemical testing.

10. The use according to claim 9, characterized in that: The conductive ion solution is selected from one or more of sodium chloride, potassium chloride, rubidium chloride, cesium chloride, magnesium chloride, strontium chloride, calcium chloride, barium chloride, potassium carbonate, potassium bicarbonate, potassium phosphate, potassium hydrogen phosphate, dipotassium hydrogen phosphate, potassium 4-hydroxyethylpiperazineethanesulfonate, and dipotassium 1,4-piperazinediethanesulfonate.